2014
DOI: 10.1186/1472-6890-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid label indicates abnormal cell development coinciding with regeneration of renal tubules

Abstract: BackgroundStem/progenitor cells are in the focus of research as a future therapeutic option to stimulate regeneration in diseased renal parenchyma. However, current data indicate that successful seeding of implanted stem/progenitor cells is prevented by harmful interstitial fluid and altered extracellular matrix. To find out possible parameters for cell adaptation, the present investigation was performed.MethodsRenal stem/progenitor cells were mounted in an artificial interstitium for perfusion culture. Exposu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…In contrast to previous series ( Figure 2 a,b, Figure 3 a,b and Figure 4 a,b), the epithelium shows after fixation in GA solution containing tannic acid a heterogeneously composed cell population as it was earlier described [ 13 ]. The one type of cells exhibits a bright cytoplasm, while the other type shows a dark-grey cytoplasm.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…In contrast to previous series ( Figure 2 a,b, Figure 3 a,b and Figure 4 a,b), the epithelium shows after fixation in GA solution containing tannic acid a heterogeneously composed cell population as it was earlier described [ 13 ]. The one type of cells exhibits a bright cytoplasm, while the other type shows a dark-grey cytoplasm.…”
Section: Resultscontrasting
confidence: 77%
“…For first orientation, semithin sections of specimens were performed as it was earlier described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither the extended basal lamina nor the heterogenously composed epithelium consisting of bright and dark cells is observed in intact renal parenchyma. Since in none of the cases a coincidence is found, unveiled morphological details in generated tubules have to be ascribed to atypical cell development as it was recently described [35,36].…”
Section: A Closer Look Reveals Atypical Cell Featuresmentioning
confidence: 97%
“…In this coherence it makes no difference, whether atypical cell development is caused by here presented culture conditions or is evoked by harsh environment of diseased parenchyma after implantation. Irrespectively of whether it may be induced by culture conditions or evoked by the environment after implantation, it is shown that in renal stem/ progenitor cells principally both intact formation of tubules and a sleeping capacity for development of atypical cell and extracellular matrix is contained [35,36].…”
Section: Disappointment Meets Responsibilitymentioning
confidence: 99%